Historicising the novel :|Madonna in a Fur Coat as a literary event - İnce, Meryem Selva. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
Madonna in a Fur Coat novel is an exceptional literary event. It is accepted as a literary document and gained an aesthetic value by getting popular in time through the appreciation of ordinary readers, even though it didn’t arouse interest in its publishing year 1943. At this point, instead of looking for an answer for why did this novel became a bestseller in 2000’s, focusing on its transformations by historicizing the novel is significant to show the elements that specifies the aesthetic category of the text. In this thesis, “Aesthetic of Reception”, historiography and intersection points with literature sociology is evaluated. The reader is positioned, by being historicized on two different class practices as “cultural nobility” and “ordinary reader” with reference to conceptualization in Bourdieu’s Distinction (1979), in the context of different reception practices and the effect of these practices on the positioning of writer and the novel. Hence, the “cultural nobility” definition in this thesis includes literary critics, historians and editors, “ordinary reader” includes the actors who use or reproduce a text that is in the information field produced by the other class. Jerome Mc Gann's (1991) "editorial horizon" conception is evaluated with novel's after 80's publishing adventure in the context of the presentation of the text to ordinary reader's effect on reader's reception. Government, publishers, periodical publications and school establishments on the other hand, are evaluated as establishments that carry the critical and historical discourse of the text’s period and also transfer or delimitate the produced semantics of the text.